Penerapan Pendekatan Sistem Dalam Manajemen Kelas Untuk Meningkatkan Disiplin Siswa Di Sekolah Dasar Negeri 106161 Laut Dendang - Maulidayani Maulidayani; Wardah Sahrani Sibarani; Elsa Elitia Hasibuan; Azra Humaira; Amaluddin Tanjung (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
The purpose of this research is to describe classroom management planning, implementation of classroom management, supervision of classroom management and supporting and inhibiting factors for classroom management in improving student learning. This research method is descriptive qualitative. The results of the research show that class management planning is carried out by arranging facilities, teaching management and student arrangements, implementation of class management is carried out by applying several class management principles and several approaches, supervision is carried out continuously. The results of the research show that classroom management by teachers has been implemented well, teachers with their abilities can condition the classroom optimally to achieve effective learning.